A novel bacteriocin DY4-2 produced by Lactobacillus plantarum from cutlassfish and its application as bio-preservative for the control of Pseudomonas fluorescens in fresh turbot (Scophthalmus maximus) fillets. (July 2018) - Lv, Xinran; Ma, Huanhuan; Sun, Mengtong; Lin, Yang; Bai, Fengling; Li, Jianrong; Zhang, Bolin
Abstract: A novel bacteriocin DY4-2 was produced by strain DY4-2 which was isolated from cutlassfish ( Trichiurus lepturus ) and identified as Lactobacillus plantarum . This bacteriocin reached the maximum production at stationary phase after 24 h incubation. It was purified by ethyl acetate extraction followed by ultrafiltration, Sephadex G25 chromatography and high-performance liquid chromatography. The molecular mass of bacteriocin DY4-2 was determined as 1465 Da by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) analysis. The amino acid sequence of bacteriocin DY4-2 was predicted to be HAQIGMTMNGSFR by MALDI-TOF-MS/MS. Bacteriocin DY4-2 was heat-stable (30 min at 121 °C) and kept active at the pH range of 2.5–5.5, but was sensitive to proteolytic enzymes. The mode of action of bacteriocin DY4-2 was bactericidal. It exhibited broad spectrum antimicrobial activity against fish pathogenic and spoilage bacteria, such as Pseudomonas fluorescens, P. aeruginosa, Vibrio parahaemolyticus, Aeromonas sobria and Listeria monocytogenes . The addition of partially purified bacteriocin DY4-2 in turbot fillets reduced the number of P. fluorescens by 2.7 log units at 4 °C storage for 12 days. Moreover, compared to the control, a significant decline in total viable counts and total volatile base nitrogen was observed in bacteriocin DY4-2 treated samples. Theses results suggested that bacteriocin DY4-2 had potential to act as seafood bio-preservative. Highlights: A novel bacteriocin was purified and characterized. The bacteriocin had a broad inhibitory spectrum. The bacteriocin had the potential to act as biopreservatives for aquatic products.